Analisis Kasus Hoaks di Kalangan Pelajar Sebagai Tantangan Literasi Digital dalam Dunia Pendidikan - Nabilah Khairunnisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study discusses the phenomenon of hoaxes among students as one of the challenges to digital literacy in the education sector. The rapid growth of digital technology and social media has made information easier for students to access. However, this development also increases the spread of false information and hoaxes among young people. This research used a qualitative approach whit a literature study method by riviewing various publications related to digital literacy and misinformation. The findings show that the apread of hoaxes among students is caused by several factors, such as limited digital literacy skills, emotional influences, social enviroments, technological developments. And weak critical thingking abilities. In addition, social media algorithms and digital culture also play an important role in accelerating the spread of misleading information. Therefore, strengthening digital literacy is considered important as a preventive effort, especially through improving critical thingking skills, information verification abilities, and ethical awareness ehwn using digital media. The study concludes that cooperation between schools, families, government, and socienty is necessary to improve students’ digital literacy skills so that the spread of hoaxes in the digital era can be reduced.